An Enigmatic Case of Acute Mercury Poisoning: Clinical, Immunological Findings and Platelet Function - Kleffner, Ilka; Eichler, Susann; Ruck, Tobias; Schüngel, Lisa; Pfeuffer, Steffen; Polzer, Philipp; Dittrich, Ralf; Dziewas, Rainer; Gross, Catharina C.; Göbel, Kerstin; Wiendl, Heinz; Kehrel, Beate E.; et al. (Frontiers in Neurology, 2017)
Severe mercury intoxication is very rare in developed countries, but still occurs as the result of volatile substance abuse, suicide attempts, occupational hazards, or endemic food ingestion as reported in the cases of public health disasters in Iraq and in Minamata Bay, Japan. Here, we describe the dramatic physical and cognitive decline of a 23-year-old patient caused by a severe methyl mercury intoxication of unknown origin. We show serial magnetic resonance imaging (MRI) of the patient’s brain, as well as ex vivo analyses of blood and cerebrospinal fluid including multicolor flow cytometric measurements, functional assays of hemostaseologic efficacy and evaluation of regulatory effector molecules. Together with the clinical history, our findings show the progressive neuronal degeneration accompanying the deterioration of the patient. Moreover, the ex vivo analyses display alterations of thrombocyte function and coagulation, as well as an immunological milieu facilitating autoimmunity. Despite the successful reduction of the methyl mercury concentration in the patient’s blood with erythrocyte apheresis and chelator therapy, his condition did not improve and led to a persistent vegetative state. This case illustrates the neurotoxicity of methyl mercury following severe intoxication for the first time by serial MRI. Data on immune-cell and thrombocyte function as well as on coagulation in mercury poisoning reveal potential implications for anticoagulation and immunomodulatory treatment.